OCEANIC OXYGEN-18 AT THE PRESENT DAY AND LGM: EQUILIBRIUM SIMULATIONS WITH A COUPLED CLIMATE MODEL OF INTERMEDIATE COMPLEXITY - Roche D.; Paillard D.; Hoffmann G.; Ganopolski A. (My University, 2004)
An Earth system model of intermediate complexity, CLIMBER-2, is used to simulate the oxygen-18 content of the water masses (H182O) in the oceans. Firstly, we forced CLIMBER-2 with the fluxes from the atmospheric general circulation model ECHAM. Simulated oceanic 18O fields for the present day are in good agreement with data. Secondly, a water isotope module was developed to transport δ18O in the atmosphere on a large scale and compute the 18O fluxes to the ocean at the atmosphere–ocean interface using only variables already computed by CLIMBER-2. For the present day, we successfully represent oxygen-18 distribution in the Atlantic, Indian and Pacific oceans, and close agreement is also found when we compare modelled and observed δ18Ow:salinity relationships. During the Last Glacial Maximum (LGM), we find that the major differences in the 18O oceanic fields (apart from the global oceanic enrichment due to ice-sheet build-up) are due to surface condition changes (surface temperature, shift in bottom water formation zones) and that no drastic changes occurred in the δ18Ow:salinity spatial relationship. In addition, we compute a calcite δ18Oc field for the Atlantic and compare it to the available data to assess the variation between the LGM and the present day.